2017
DOI: 10.3758/s13414-017-1423-5
|View full text |Cite
|
Sign up to set email alerts
|

Do age and linguistic background alter the audiovisual advantage when listening to speech in the presence of energetic and informational masking?

Abstract: We examined how the type of masker presented in the background affected the extent to which visual information enhanced speech recognition, and whether the effect was dependent on or independent of age and linguistic competence. In the present study, young speakers of English as a first language (YEL1) and English as a second language (YEL2), as well as older speakers of English as a first language (OEL1), were asked to complete an audio (A) and an audiovisual (AV) speech recognition task in which they listene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
(134 reference statements)
4
8
0
Order By: Relevance
“…Although children demonstrated AV benefit in the TTS, the magnitude of benefit was no greater than in the SSN. In contrast, each adult who did not reach ceiling demonstrated greater AV benefit in the TTS than in the SSN, replicating previous findings ( Avivi-Reich et al , 2018 ; van Engen et al , 2014 ; Helfer and Freyman, 2005 ). The results of the current study contrast with Lalonde and McCreery (2020) , which showed that 6- to 12-year-old children and adults benefited five times more from visual speech on a syllable detection task in a TTS than in an SSN.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although children demonstrated AV benefit in the TTS, the magnitude of benefit was no greater than in the SSN. In contrast, each adult who did not reach ceiling demonstrated greater AV benefit in the TTS than in the SSN, replicating previous findings ( Avivi-Reich et al , 2018 ; van Engen et al , 2014 ; Helfer and Freyman, 2005 ). The results of the current study contrast with Lalonde and McCreery (2020) , which showed that 6- to 12-year-old children and adults benefited five times more from visual speech on a syllable detection task in a TTS than in an SSN.…”
Section: Discussionsupporting
confidence: 87%
“…Visual speech is a stimulus characteristic known to promote grouping in adults ( Helfer and Freyman, 2005 ). Adults benefit more from visual speech cues in the presence of speech maskers than in spectrally matched noise maskers ( Avivi-Reich et al , 2018 ; van Engen et al , 2017 ; Helfer and Freyman, 2005 ). Whereas visual speech provides supplemental phonetic information in both maskers (i.e., visual cues to place of articulation when acoustic place cues are masked), visual speech also helps adults to perceptually separate target speech from the mixture of voices in the speech masker ( Helfer and Freyman, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The result that the effects of a timbre contrast (T D M C -T C M D ) are larger for informational maskers (Babble and Speech) than they are for a Noise masker is consistent with the general result found for stimulus conditions that produce a release from masking (Avivi-Reich et al, 2018;Ezzatian, et al, 2010;Freyman et al, 2004). The difference here is that the direction of the contrast effect depends on whether the target is compact versus when it diffuse.…”
Section: Signal-to-noise (Snr) Thresholds and Performancesupporting
confidence: 87%
“…This type of interference, which is often referred to as informational masking, can occur independently of energetic masking (Durlach et al, 2003;Freyman, Helfer, McCall, & Clifton, 1999;Kidd, Mason, Richards, Gallun, & Durlach, 2008;Schneider, Pichora-Fuller, & Daneman, 2010;Schneider, Li, & Daneman, 2007). Based on the results of previous studies that have examined the differences between energetic and informational masking, we would expect the benefit obtained from a contrast in timbre to be larger when the masker causes substantial informational masking rather than when the masker is primarily energetic (e.g., Arbogast, Mason, & Kidd, 2002;Avivi-Reich, Puka, & Schneider, 2018;Ezattian, Avivi, & Schneider, 2010;Freyman, Balakrishnan, & Helfer, 2004). With respect to the current study, we might expect a timbre contrast to produce a greater release from masking when the masker is babble or competing speech than when the masker is steady-state noise.…”
Section: Auditory Streaming: Energetic and Informational Maskingmentioning
confidence: 99%
“…Accordingly, older and younger adults benefit from visible speech when perceiving SiN, both on a behavioral (e.g. Avivi-Reich et al, 2018 ; Smayda et al, 2016 ; Sommers et al, 2005 ; Stevenson et al, 2015 ; Tye-Murray et al, 2010 ; 2016 ) and on an electrophysiological level (Winneke & Phillips, 2011 ). The size of the benefit depends on the quality of the acoustic speech signal, or signal-to-noise ratio (SNR), as well as on individual auditory and visual perception and processing abilities (Tye-Murray et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%